2020
DOI: 10.31048/1852.4826.v13.n1.23828
|View full text |Cite
|
Sign up to set email alerts
|

La variabilidad morfológica en raspadores en el centro-oeste de Santa Cruz, Patagonia meridional. Su evaluación en términos temporales

Abstract: RMA La variabilidad morfológica en raspadores en el centro-oeste de Santa Cruz, Patagonia meridional. Su evaluación en términos temporales Endscrapers morphological variability in central-western of Santa Cruz province, Southern Patagonia. A temporal evaluation Resumen En este trabajo evaluamos comparativamente raspadores del Holoceno medio y tardío del centro-oeste de Santa Cruz (Patagonia) a los fines de discutir acerca de la variabilidad de los conjuntos en el contexto de cambios ambientales que se dieron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The specific characteristics of structures and the hunting strategies in which they were involved were discussed in previous works (Aragone & Cassiodoro 2006;Aragone et al 2010;Cassiodoro 2011: 171;2019;Dellepiane 2019: 320;Flores Coni 2014;2019, Flores Coni et al 2021Goñi et al 2011Goñi et al -20122016, among others). The analysis based on site scales revealed that some structures were clearly related to hunting per se while others were related to more general activities and may have also functioned as temporal residential camps (Cassiodoro 2011: 171;Dellepiane 2019: 320;Flores Coni 2019a). The latter was also suggested for structures in Somuncurá Plateau, in northern Patagonia (Gradin 1971;Miotti et al 2016).…”
Section: Stone Structuresmentioning
confidence: 97%
See 3 more Smart Citations
“…The specific characteristics of structures and the hunting strategies in which they were involved were discussed in previous works (Aragone & Cassiodoro 2006;Aragone et al 2010;Cassiodoro 2011: 171;2019;Dellepiane 2019: 320;Flores Coni 2014;2019, Flores Coni et al 2021Goñi et al 2011Goñi et al -20122016, among others). The analysis based on site scales revealed that some structures were clearly related to hunting per se while others were related to more general activities and may have also functioned as temporal residential camps (Cassiodoro 2011: 171;Dellepiane 2019: 320;Flores Coni 2019a). The latter was also suggested for structures in Somuncurá Plateau, in northern Patagonia (Gradin 1971;Miotti et al 2016).…”
Section: Stone Structuresmentioning
confidence: 97%
“…Parapetos may be found isolated or in groups of two or more structures with scarce metres of distance in between. Some exceptional sites have been recorded with more than 10 structures associated in each of the areas under study (except Asador Plateau) (Cassiodoro et al 2016;Flores Coni 2014;2019a;Goñi et al 2016). As for their emplacement, it is variable and there is no clear pattern.…”
Section: Stone Structuresmentioning
confidence: 98%
See 2 more Smart Citations